Pedigree analysis of pre-breeding efforts in Trifolium spp. germplasm in New Zealand - L. M. Egan; R. W. Hofmann; P. Seguin; K. Ghamkhar; V. Hoyos-Villegas (BMC Genetics, 2020)
Abstract Background Prebreeding in plants is the activity designed to identify useful characteristics from wild germplasm and its integration in breeding programs. Prebreeding aims to introduce new variation into the populations of a species of interest. Pedigree analysis is a valuable tool for evaluation of variation in genebanks where pedigree maps are used to visualize and describe population structure and variation within these populations. Margot Forde Germplasm Centre (MFGC) is New Zealand’s national forage genebank and holds a collection of ~ 75 species of the genus Trifolium, of which only a dozen have been taken through prebreeding programs. The main objective of this study was to construct pedigree maps and analyse patterns of relatedness for seven minor Trifolium species accessions contained at the MFGC. These species are Trifolium ambiguum, Trifolium arvense, Trifolium dubium, Trifolium hybridum, Trifolium medium, Trifolium subterraneum and the Trifolium repens x Trifolium occidentale interspecific hybrids. We present a history of Trifolium spp. prebreeding in New Zealand and inform breeders of possible alternative forage species to use. Results Pedigree data from accessions introduced between 1950 and 2016 were used and filtered based on breeding activity. Kinship levels among Trifolium spp. remained below 8% and no inbreeding was found. Influential ancestors that contributed largely to populations structure were identified. The Australian cultivar ‘Monaro’ had a strong influence over the whole population of accessions in T. ambiguum. T. subterraneum and T. repens x T. occidentale had the largest number of generations (3). T. ambiguum and T. medium had the highest cumulative kinship across the decades. Conclusions We conclude that there are high levels of diversity in the seven Trifolium spp. studied. However, collection and prebreeding efforts must be strengthened to maximize utilization and bring useful genetic variation.